The burning : a novel - Kellerman, Jonathan; Kellerman, Jesse (Ballantine Books, 2021)
"Things get personal for Deputy Coroner Clay Edison when a murder hits close to home in this riveting, emotional thriller from the bestselling father-son team who write "brilliant, page-turning fiction" (Stephen King). A raging wildfire. A massive blackout. A wealthy man shot to death in his palatial hilltop home. For Clay Edison, it's all in a day's work. As a deputy coroner, caring for the dead, he speaks for those who cannot speak for themselves. He prides himself on an unflinching commitment to the truth. Even when it gets him into trouble. Then, while working the murder scene, Clay is horrified to discover a link to his brother, Luke. Horrified. But not surprised. Luke is fresh out of prison and struggling to stay on the straight and narrow. And now he's gone AWOL. The race is on for Clay to find him before anyone else can. Confronted with Luke's legacy of violence, Clay is forced to reckon with his own suspicions, resentments, and loyalties. Is his brother a killer? Or could he be the victim in all of this, too? This is Jonathan and Jesse Kellerman at their most affecting and page-turning-a harrowing collision of family, revenge, and murder"--